IoT-Based Home Security System: ESP32-CAM Integration and Real-Time Notification - Qori Halimatul Hidayah; Ryan Putra Laksana; Ary Prabowo; Dwi Santika Simatupang (International Transactions on Education Technology (ITEE), 2026)
Conventional home security systems are generally unable to provide real-time monitoring accompanied by visual evidence when suspicious activity occurs, so the user response rate is still low. The development of the Internet of Things (IoT) allows the integration of sensors, cameras and communication platforms to produce more adaptive and responsive security systems. This research aims to develop a prototype IoT-based home security system using ESP32-CAM and PIR sensors integrated with the Telegram Bot API to provide image-based au- tomatic notifications. The research was carried out through the stages of needs identification, literature study, design, prototype development, and functional testing. The system is designed to detect movement via a PIR sensor, take im- ages using the ESP32-CAM, store them on MicroSD media, and send real-time notifications to users via the Telegram platform. Test results show that the sys- tem is able to detect movement accurately, take images with stable quality, and send notifications with a 100% success rate as long as a network connection is available. Moreover, there is also the provision of manually executing /takefoto commands for remotely monitoring the system. This research work contributes towards designing a home security system which is not only cost-effective but is also relatively simple to implement and highly adaptable in the community environment. Future development could involve cloud data storage and video recording capabilities.